Lithium‐Sulfur Batteries: Hierarchical Vine‐Tree‐Like Carbon Nanotube Architectures: In‐Situ CVD Self‐Assembly and Their Use as Robust Scaffolds for Lithium‐Sulfur Batteries (Adv. Mater. 41/2014). (November 2014) - Zhao, Meng‐Qiang; Peng, Hong‐Jie; Tian, Gui‐Li; Zhang, Qiang; Huang, Jia‐Qi; Cheng, Xin‐Bing; Tang, Cheng; Wei, Fei
<x xml:space="preserve">Abstract</x> Hierarchical vine‐tree‐like carbon nanotube architectures composed of vine‐like single‐walled carbon nanotubes wrapping around the tree‐like multi‐walled carbon nanotubes are represented that are fabricated through in‐situ chemical vapor deposition self‐assembly, as reported by Q. Zhang, F. Wei, and co‐workers on page 7051. Such biomimetic nanoarchitectures exhibit excellent performance when employed as the cathode scaffolds for lithium‐sulfur batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>